Porcine aminopeptidase N binds to F4(+) enterotoxigenic Escherichia coli fimbriae - Xia, P. P.; Wang, Y. T.; Zhu, C. R.; Zou, Y. J.; Yang, Y.; Liu, W.; Hardwidge, Philip R.; Zhu, G. Q. (My University, 2016)
F4(+) enterotoxigenic Escherichia coli (ETEC) strains cause diarrheal disease in neonatal and post-weaned piglets. Several different host receptors for F4 fimbriae have been described, with porcine aminopeptidase N (APN) reported most recently. The FaeG subunit is essential for the binding of the three F4 variants to host cells. Here we show in both yeast two-hybrid and pulldown assays that APN binds directly to FaeG, the major subunit of F4 fimbriae, from three serotypes of F4(+) ETEC. Modulating APN gene expression in IPEC-J2 cells affected ETEC adherence. Antibodies raised against APN or F4 fimbriae both reduced ETEC adherence. Thus, APN mediates the attachment of F4(+) E. coli to intestinal epithelial cells.
Citation: Xia, P. P., Wang, Y. T., Zhu, C. R., Zou, Y. J., Yang, Y., Liu, W., . . . Zhu, G. Q. (2016). Porcine aminopeptidase N binds to F4(+) enterotoxigenic Escherichia coli fimbriae. Veterinary Research, 47, 7. doi:10.1186/s13567-016-0313-5
Keywords: F4 Fimbriae; Brush-Borders; In-Vitro; Adhesin Variants; Receptor-Binding; Epithelial-Cell